'Part of our DNA': intergenerational family learning in informal science. Issue 4 (2nd October 2022) - Simmons, Jon; Campbell, Todd; Moss, David M.; Volin, John C.; Arnold, Chester; Cisneros, Laura M.; Chadwick, Cary; Dickson, David; Freidenfelds, Nicole
ABSTRACT: Families create contexts for learning to enhance and support the interests of their children, while simultaneously teaching language, morals, and culture. This research examines intergenerational family teams engaged in a long-term conservation project in their community. Participants were interviewed during and after project completion with the central research purpose of exploring how the intersecting experiences of family members explain emerging family cultural learning pathways. Intergenerational family teams shared narratives which were then analyzed using the cultural learning pathways framework [Bell, P., Tzou, C., Bricker, L., & Baines, A. D. (2012). Learning in diversities of structures of social practice: Accounting for how, why and where people learn science. Human Development, 55(5-6), 269–284. doi:10.1159/000345315 ] that we subsequently used to create family cultural learning pathways for each participating family. Family interactions are powerful influences on the identity development of children, not only in their academic development, but also in their moral, ethical, and social development.